SUMO control of centromere homeostasis - van den Berg, Sebastiaan J. W.; Jansen, Lars E. T. (Frontiers in Cell and Developmental Biology, 2023)
Centromeres are unique chromosomal loci that form the anchorage point for the mitotic spindle during mitosis and meiosis. Their position and function are specified by a unique chromatin domain featuring the histone H3 variant CENP-A. While typically formed on centromeric satellite arrays, CENP-A nucleosomes are maintained and assembled by a strong self-templated feedback mechanism that can propagate centromeres even at non-canonical sites. Central to the epigenetic chromatin-based transmission of centromeres is the stable inheritance of CENP-A nucleosomes. While long-lived at centromeres, CENP-A can turn over rapidly at non-centromeric sites and even erode from centromeres in non-dividing cells. Recently, SUMO modification of the centromere complex has come to the forefront as a mediator of centromere complex stability, including CENP-A chromatin. We review evidence from different models and discuss the emerging view that limited SUMOylation appears to play a constructive role in centromere complex formation, while polySUMOylation drives complex turnover. The deSUMOylase SENP6/Ulp2 and the proteins segregase p97/Cdc48 constitute the dominant opposing forces that balance CENP-A chromatin stability. This balance may be key to ensuring proper kinetochore strength at the centromere while preventing ectopic centromere formation.